Analysis of Coordinated Motions of Humanoid Robot Fingers Using Interphalangeal Joint Coordination. (28th April 2014) - Kim, Byoung-Ho
In this study, we analyse the coordinated motions of humanoid robot fingers using an interphalangeal joint coordination. For this purpose, four humanoid robot fingers with different sizes have been considered. A biomimetic interphalangeal joint coordination (IJC) formulation based on the grasp configuration of human fingers has been presented for humanoid robot fingers. The usefulness of the specified IJC formulation for human-like finger motion has been verified through comparative demonstrations. As a result, a proper coordination of humanoid robot fingertips can be achieved by applying our IJC formulation. Also the IJC formulation can be used to design of humanoid robot fingers.